Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Let's solve the equation \(\log_{256} (2x - 1) = 8\) step by step.
1. Understanding the Logarithmic Equation:
The equation given is \(\log_{256} (2x - 1) = 8\). This means that \(256\) raised to the power of \(8\) equals \(2x - 1\).
2. Converting the Logarithmic Equation to an Exponential Equation:
[tex]\[ 256^8 = 2x - 1 \][/tex]
3. Simplifying the Exponential Expression:
Now we need to simplify \(256^8\).
Notice that \(256\) can be written as \(2^8\) because:
[tex]\[ 256 = 2^8 \][/tex]
Therefore,
[tex]\[ 256^8 = (2^8)^8 \][/tex]
4. Further Simplify Using Power Rules:
Using the power rule \((a^m)^n = a^{m \cdot n}\), we get:
[tex]\[ (2^8)^8 = 2^{64} \][/tex]
5. Substitute Back:
So now we have:
[tex]\[ 2x - 1 = 2^{64} \][/tex]
6. Solving for \(x\):
To isolate \(x\), we add \(1\) to both sides of the equation:
[tex]\[ 2x = 2^{64} + 1 \][/tex]
Then, divide by \(2\) to solve for \(x\):
[tex]\[ x = \frac{2^{64} + 1}{2} \][/tex]
7. Simplifying the Expression:
This simplifies to:
[tex]\[ x = \frac{2^{64}}{2} + \frac{1}{2} = 2^{63} + \frac{1}{2} \][/tex]
8. Final Answer:
As simplified, we have:
[tex]\[ x = \frac{257}{2} \][/tex]
Therefore, the solution to the equation \(\log_{256} (2x - 1) = 8\) is:
[tex]\[ x = \frac{257}{2} \][/tex]
1. Understanding the Logarithmic Equation:
The equation given is \(\log_{256} (2x - 1) = 8\). This means that \(256\) raised to the power of \(8\) equals \(2x - 1\).
2. Converting the Logarithmic Equation to an Exponential Equation:
[tex]\[ 256^8 = 2x - 1 \][/tex]
3. Simplifying the Exponential Expression:
Now we need to simplify \(256^8\).
Notice that \(256\) can be written as \(2^8\) because:
[tex]\[ 256 = 2^8 \][/tex]
Therefore,
[tex]\[ 256^8 = (2^8)^8 \][/tex]
4. Further Simplify Using Power Rules:
Using the power rule \((a^m)^n = a^{m \cdot n}\), we get:
[tex]\[ (2^8)^8 = 2^{64} \][/tex]
5. Substitute Back:
So now we have:
[tex]\[ 2x - 1 = 2^{64} \][/tex]
6. Solving for \(x\):
To isolate \(x\), we add \(1\) to both sides of the equation:
[tex]\[ 2x = 2^{64} + 1 \][/tex]
Then, divide by \(2\) to solve for \(x\):
[tex]\[ x = \frac{2^{64} + 1}{2} \][/tex]
7. Simplifying the Expression:
This simplifies to:
[tex]\[ x = \frac{2^{64}}{2} + \frac{1}{2} = 2^{63} + \frac{1}{2} \][/tex]
8. Final Answer:
As simplified, we have:
[tex]\[ x = \frac{257}{2} \][/tex]
Therefore, the solution to the equation \(\log_{256} (2x - 1) = 8\) is:
[tex]\[ x = \frac{257}{2} \][/tex]
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.